2011
DOI: 10.1590/s0100-06832011000300035
|View full text |Cite
|
Sign up to set email alerts
|

Erosão hídrica associada a algumas variáveis hidrológicas em pomar de maçã submetido a diferentes manejos do solo

Abstract: RESUMOO manejo do solo em cultivos perenes, como pomares, influencia a erosão hídrica. O presente estudo avaliou as perdas de solo e água sob chuva simulada em um Latossolo, em pomar de maçã, entre os meses de agosto de 2007 e abril de 2008, na estação experimental de fruticultura de clima temperado da Embrapa Uva e Vinho, em Vacaria (RS). O trabalho foi conduzido em parcelas experimentais de 3,5 x 11 m, sob chuvas com 1 h de duração e intensidade constante ao longo delas, com variação de 70 a 88 mm h -1 entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
5
3
0
6
Order By: Relevance
“…Thus, climate and crop growing variations over the time of the experiment, and water consumption by crops, influenced the time needed for the beginning of surface runoff from the applied rainfall tests. Similar data were observed in other studies (Gray & Cogo, 1980;Luciano et al, 2009;Gobbi et al, 2011;Barbosa et al, 2012). …”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Thus, climate and crop growing variations over the time of the experiment, and water consumption by crops, influenced the time needed for the beginning of surface runoff from the applied rainfall tests. Similar data were observed in other studies (Gray & Cogo, 1980;Luciano et al, 2009;Gobbi et al, 2011;Barbosa et al, 2012). …”
Section: Resultssupporting
confidence: 91%
“…Most of the rain intensities were quite close to the planned value (64 mm h -1 ), except for the rain of Test 3, under the soybean and corn/ common bean treatments, whose value was 13 % higher than the planned intensity. Variations between applied and planned simulated rainfall intensities are normal in such studies, as reported by Bertol et al (2008), Luciano et al (2009) and Gobbi et al (2011).…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations